Efficient visible-light photocatalytic H2 evolution over metal-free g-C3N4 co-modified with robust acetylene black and Ni(OH)2 as dual co-catalysts. Issue 37 (29th March 2016) - Bi, Guican; Wen, Jiuqing; Li, Xin; Liu, Wei; Xie, Jun; Fang, Yueping; Zhang, Weiwei
Abstract : Enhanced photocatalytic visible-light H2 -evolution activity over metal-free g-C3 N4 co-modified with acetylene black and Ni(OH)2 co-catalysts is reported. Abstract : In this work, a novel g-C3 N4 /acetylene black (AB)/Ni(OH)2 ternary composite photocatalyst with dual robust electron co-catalysts was successfully synthetized using a facile two-step strategy: ultrasonic dispersion treatment and a subsequent precipitation process. The photocatalytic H2 -production activity over the composite photocatalyst was also evaluated using an aqueous solution containing triethanolamine under visible light ( λ ≥ 420 nm). For the first time, it was revealed that the robust AB can be utilized as a co-catalyst to significantly enhance the photocatalytic H2 -evolution activity of g-C3 N4 . The results also demonstrated that the ternary g-C3 N4 /AB/Ni(OH)2 nanocomposite exhibited enhanced photocatalytic H2 -evolution activity as compared to bulk g-C3 N4 and binary hybrids. The g-C3 N4 –0.5% AB–1.0% Ni(OH)2 (weight ratio) composite shows the highest H2 evolution rate of 240 μmol g −1 h −1 under visible light irradiation, which is 320, 100 and 3.31 times higher than that of pure g-C3 N4, g-C3 N4 –0.5% AB and g-C3 N4 –1.0% Ni(OH)2, respectively. It is believed that the excellent synergetic effect between the robust AB and Ni(OH)2 as dual electron co-catalysts on the surface of g-C3 N4 can achieve the effectively promoted separation of photo-generated electron–hole pairs and enhance the following H2 -evolution kinetics, thus resulting in a significant enhancement of the photocatalytic H2 evolution activity over g-C3 N4 . It is expected that the combination of nano-carbons such as AB and other earth-abundant co-catalysts can become a general strategy to improve the H2 -evolution activity over various kinds of conventional semiconductors.